2004
DOI: 10.1161/01.res.0000122141.18795.9c
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres and Cardiovascular Disease

Abstract: Abstract-Telomeres-the specialized DNA-protein structures at the ends of eukaryotic chromosomes-are essential for maintaining genome stability and integrity and for extended proliferative life span in both cultured cells and in the whole organism. Telomerase and additional telomere-associated proteins are necessary for preserving telomeric DNA length. Age-dependent telomere shortening in most somatic cells, including vascular endothelial cells, smooth muscle cells, and cardiomyocytes, is thought to impair cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(160 citation statements)
references
References 98 publications
5
153
0
2
Order By: Relevance
“…Telomere maintenance has relevance for long-term health. Shortened telomere length and/or reduced telomerase activity have been consistently associated with health risk and diseases (12)(13)(14)(15). Declines in the telomere/telomerase maintenance system may play a causal role in aging, serve as a biomarker of aging, or both.…”
Section: Developmental Programming | Fetal Originmentioning
confidence: 99%
“…Telomere maintenance has relevance for long-term health. Shortened telomere length and/or reduced telomerase activity have been consistently associated with health risk and diseases (12)(13)(14)(15). Declines in the telomere/telomerase maintenance system may play a causal role in aging, serve as a biomarker of aging, or both.…”
Section: Developmental Programming | Fetal Originmentioning
confidence: 99%
“…134,135 Inhibition of nuclear TERT activity shortens telomere length, leading to decrease in the endothelial cell's life span, alteration in gene expression and change from phenotype of young cells to phenotype of old cells. 136 In addition, telomere shortening stimulates activation of p53, p21 and p16 proteins, which are triggers of cell senescence. 137,138 The endogenous eNOS inhibitor asymmetrical dimethylarginine also accelerates endothelial cell senescence through increase in production of ROS and inhibition of NO production.…”
Section: Endothelial Cell Senescencementioning
confidence: 99%
“…TERT-expressing cells show extensive changes in gene expression patterns; the ability of hTERT to exert a variety of effects that counteract cell death is striking (Sung et al, 2005) and these effects have been reported also in whole animals overexpressing TERT; in mice this protects against experimental heart failure ( Oh et al, 2001) and has many other effects in the cardiovascular system (Serrano and Andres, 2004). hTERT-expressing cells are more resistant to chromosome damage caused by ionizing radiation (Pirzio et al, 2004).…”
Section: The Potential Role Of Telomerase In Cell Therapy In Agingmentioning
confidence: 99%